Sterile marginal flowers increase visitation and fruit set in the hobblebush (Viburnum lantanoides, Adoxaceae) at multiple spatial scales. (30th June 2018) - Park, Brian; Sinnott-Armstrong, Miranda; Schlutius, Caroline; Zuluaga, Juan-Carlos Penagos; Spriggs, Elizabeth L; Simpson, Raymond G; Benavides, Edgar; Landis, Michael J; Sweeney, Patrick W; Eaton, Deren A R; Donoghue, Michael J
Abstract: Background and Aims: Enlarged sterile flowers on the periphery of inflorescences increase the attractiveness of floral displays, and previous studies have generally demonstrated that these have positive effects on insect visitation and/or reproductive success. However, experiments have not specifically been designed to examine the benefits of sterile flowers under conditions that reflect the early stages in their evolution, i.e. when plants that produce sterile flowers are at low frequency. Methods: Over three years, three experiments were performed in natural populations of Viburnum lantanoides, which produces sterile marginal flowers (SMFs). The first experiment established that fruit production in V. lantanoides increases with the receipt of outcross pollen. The second tested the role of SMFs under extant conditions, comparing fruit production in two populations composed entirely of intact plants or entirely of plants with the SMFs removed. The third was designed to mimic the presumed context in which SMFs first evolved; here, SMFs were removed from all but a few plants in a population, and rates of insect visitation and fruit set were compared between plants with intact and denuded SMFs. Key Results: In comparing whole populations, the presence of SMFs nearly doubled fruit set. Under simulated 'ancestral' conditions within a population, plants with intact SMFs received double the insect visits and produced significantly more fruits than denuded plants. There was no significant effect of the number of inflorescences or fertile flowers on insect visitation or fruit set, indicating that the presence of SMFs accounted for these differences. Conclusions: The presence of SMFs significantly increased pollinator attraction and female reproductive success both in contemporary and simulated ancestral contexts, indicating that stabilizing selection is responsible for their maintenance, and directional selection likely drove their evolution when they first appeared. This study demonstrates a novel approach to incorporating historically relevant scenarios into experimental studies of floral evolution.